Wielka Izba i jej rola w kształtowaniu Europejskiego Trybunału Praw Człowieka: [The Grand Chamber and its role in creation of the case-law of The European Court of Human Rights] (Studia Prawnicze / The Legal Studies, 2011)
Utworzony w ramach Rady Europy na mocy Europejskiej Konwencji Praw Człowieka z 1950 r. (KE) Europejski Trybunał Praw Człowieka (ETPCz) stał się pierwszym i jedynym stricte sądowym organem, upoważnionym do rozpatrywania skarg na naruszenie standardów tego traktatu. W swoim pierwotnym zamyśle był to także organ „jednoinstancyjny”, gdyż wyroki wydawane przez 7-osobowe (a od 1990 r. 9-osobowe) izby – zgodnie z art. 52 KE – uzyskiwały walor decyzji ostatecznych. Rozwiązanie to nie budziło większych wątpliwości, skoro ETPCz plasował się w kategorii ostatniego z możliwych, organu upoważnionego do kontroli na drodze dochodzenia roszczeń z tytułu naruszenia przez państwa-strony KE ich zobowiązań traktatowych. Co więcej, jako pierwszy międzynarodowy trybunał ds. ochrony praw człowieka in genere, ETPCz rozpoczynał swoją działalność w 1959 r. bez w zasadzie żadnego praktycznego punktu odniesienia. The main purpose of this research is giving an answer for the question about the role which has been already played and can be played in future by the Grand Chamber created in 1998 within the European Court of Human Rights (ECHR). Obviously the fact that wide competences and powers have been conferred on this organizational formation of the ECHR created a unique situation concerning the substantive and procedural quality of the judgments. On the other hand, there is a potential risk that the possibility of referral of a case to the Grand Chamber can also be used for the purposes other than those strictly connected with the idea of the fair and objective justice system. The Author of this paper based her analysis against the background of 272 judgments which have been passed by the Grand Chamber and in such context she tries to make a systematization of problems both of the substantive and procedural nature. In principle the Author’s attitude is positive as far as any possibility of strengthening of the individual’s position in the control procedure of ECHR is concerned. However, according to the presented analysis the Author suggests that the Grand Chamber is still a kind of “big unknown”. Thus, at present it would be still difficult to appreciate in a concluding manner, the way in which the organ under consideration uses its decision-making power. The above-mentioned dilemma does not change the fact that this new area of the ECHR case-law creates a great challenge both for the ECHR itself as well as for all those who strongly support this institution.